Embodiment and Performance in the Supernumerary Hand Illusion in Augmented Reality - Rosa, Nina; Veltkamp, Remco C.; Hürst, Wolfgang; Brouwer, Anne-Marie; Gijsbertse, Kaj; Cocu, Ioana; Werkhoven, Peter (Frontiers in Computer Science, 2021)
In teleoperations, robots are generally used because related tasks are too dangerous, uncomfortable or impossible for humans to perform. When using augmented reality to control robotic limbs in such teleoperations, it is essential to understand how these extra virtual limbs are experienced. In particular, the relationship between the embodiment experience of the user and relevant outcomes such as task performance must be examined. In this article, we study the relationship between experienced embodiment of a supernumerary virtual arm that acts alongside a user’s two real arms, and their task performance in augmented reality. Specifically, we compare how well users can trace a virtual half ring placed just outside of personal space using their virtual arm in a condition where there is expected to be low embodiment (a floating disconnected hand) and a condition where there is expected to be high embodiment (a connected arm and hand). Embodiment is measured quantitatively through skin conductance response and qualitatively through ownership, agency, and self-location questionnaires. Performance is measured in terms of tracing precision. The results show positive correlations between subjective ownership and agency, and agency and performance, but no correlation between subjective or objective ownership and performance. Also, ownership ratings were low overall, while the agency ratings were significantly higher for the disconnected hand condition than the connected arm condition, as was performance. Notably, the presence of the virtual arm evoked incorrect expectations of the movement capabilities of the arm, which may have contributed to an overall preference for the unrealistic disconnected hand over the more realistic connected arm in this particular task. Our results imply that methods to increase performance in various teleoperations can indeed be found in the experience of embodiment: not necessarily directly through ownership, but through ownership mediated by agency.